Public Opinion and Public Policy: Citizen Sensitivity and Government Responsiveness in Spain - Cicuéndez Santamaría, Ruth (Revista del CLAD Reforma y Democracia, 2021)
The congruence between social preferences and government policies has become an essential aspect of the representative democracies and the State-society relations. Based on this premise, this article explores the interaction between public opinion and public policy in Spain during the last two decades, through the empirical analysis of the relationship between citizens’ preferences public spending and spending policies. Specifically, it is studied the effect of public opinion on government decisions about the allocation of public spending in eight key policies, as well as the influence of these decisions on social demands. The article aims to answer two questions: 1) Are governments responsive to society’s preferences and are citizens sensitive to government decisions? 2) Is the level of responsiveness different depending on the public policy? The results indicate that the political decisions on spending are moderately affected by social preferences, while government actions have a limited influence on citizen demands. Moreover, the analysis shows that prior to the Great Recession of 2008, a significant level of consistency between public opinion and policy had been achieved, which was considerably reduced during the crisis. Finally, it was found that the degree of responsiveness varies significantly from one policy to another and that it is higher in welfare policies, except for the unemployment protection program.
Keywords: Public Opinion; Public Policy; Public Spending; Relations State-Society; Relations with Citizens; Spain